Age-induced changes in white, brite, and brown adipose depots: a mini-review - Schosserer, Markus; Grillari, Johannes; Wolfrum, Christian; Scheideler, Marcel (Gerontology, 2018)
Aging is a time-related process of functional decline at organelle, cellular, tissue, and organismal level that ultimately limits life. Cellular senescence is a state of permanent growth arrest in response to stress and one of the major drivers of aging and age-related disorders. Senescent cells accumulate with age, and removal of these cells delays age-related disorders in different tissues and prolongs healthy lifespan. One of the most studied aging mechanisms is the accumulation of reactive oxygen species damage in cells, organs, and organisms over time. Elevated oxidative stress is also found in metabolic diseases such as obesity, metabolic syndrome and associated disorders. Moreover, dysregulation of the energy homeostasis is also associated with aging, and many age-related genes also control energy metabolism, with the adipose organ, comprising white, brite, and brown adipocytes, as an important metabolic player in the regulation of whole-body energy homeostasis. This review summarizes transformations in the adipose organ upon aging and cellular senescence and sheds light on the reallocation of fat mass between adipose depots, on the metabolism of white and brown adipose tissue, on the regenerative potential and adipogenic differentiation capacity of preadipocytes, and on alterations in mitochondria and bioenergetics. In conclusion, the aging process is a lifelong, creeping process with gradual decline in (pre-)adipocyte function over time. Thus, slowing down the accumulation of (pre-)adipocyte damage and dysfunction, removal of senescent preadipocytes as well as blocking deleterious compounds of the senescent secretome are protective measures to maintain a lasting state of health at old age.
Published online: December 7, 2017
Gesehen am 23.04.2020